2017
DOI: 10.31219/osf.io/j5ke3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Reliability of surface facial electromyography

Abstract: Data from two studies were used to estimate the reliability of facial EMG when used to index facial mimicry (Study 1) or affective reactions to pictorial stimuli (Study 2). Results for individual muscle sites varied between muscles and depending on data treatment. For difference scores, acceptable internal consistencies were found only for corrugator supercilii, and test-retest reliabilities were low. For contrast measures describing patterns of reactions to stimuli, such as high zygomaticus major combined wit… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 33 publications
0
23
0
Order By: Relevance
“…These indexes were based on the assumption that facial mimicry is defined as the imitation of the emotional expressions of others (that is, the presence of facial mimicry implies a pattern of facial activity in response to the emotional display of others). Put differently, mimicry cannot be analysed on a muscle by muscle base but rather needs to capture the joint movement of the muscles involved in facial expressions (see Hess et al, 2017;Hess & Blairy, 2001). Specifically, for both anger and sadness, mimicry should be indexed by significantly higher levels of corrugator supercilii than zygomaticus major activity.…”
Section: Facial Emgmentioning
confidence: 99%
See 1 more Smart Citation
“…These indexes were based on the assumption that facial mimicry is defined as the imitation of the emotional expressions of others (that is, the presence of facial mimicry implies a pattern of facial activity in response to the emotional display of others). Put differently, mimicry cannot be analysed on a muscle by muscle base but rather needs to capture the joint movement of the muscles involved in facial expressions (see Hess et al, 2017;Hess & Blairy, 2001). Specifically, for both anger and sadness, mimicry should be indexed by significantly higher levels of corrugator supercilii than zygomaticus major activity.…”
Section: Facial Emgmentioning
confidence: 99%
“…Additionally, in order to differentiate between anger and sadness more precisely, we calculated an alternative facial activity index for sadness, by subtracting the activity of depressor from the activity of zygomaticus major. However, given that the electrode placement for depressor is liable to pick up the EMG signal from adjacent areas (Hess et al, 2017), analyses involving sadness mimicry would rely on the more reliable facial activity index.…”
Section: Facial Emgmentioning
confidence: 99%
“…In line with the Precision Medicine Initiative (Insel, Amara, & Baschke, ), identifying biological indicators that predict treatment response is critical. Prior to testing predictors, research must first examine core psychometric properties, including test‐retest stability (i.e., invariance over time) and internal consistency (i.e., odd/even reliability; see Auerbach et al, ; Cassidy, Robertson, & O'Connell, ; Hess et al, ; Olvet & Hajcak, ; Tenke et al, ; Weinberg & Hajcak, ). In research testing the EIT, Kujawa and colleagues (2013) showed 2‐year stability of LPP amplitude in children 8 to 13 years old.…”
Section: Introductionmentioning
confidence: 99%
“…Facial EMG is used to quantify and identify emotions often characterizing positive and negative valence (as opposed to specific emotions). Consequently, many studies focus on the acquisition of Corrugator and Zygomaticus (negative vs.positive valence respectively; see (Larsen & Fredrickson, ), in part due to increased reliability of these signals when compared with emotion specific signals (Hess et al, ). The results indicated that Corrugator response discriminates negative facial stimuli (i.e., ‘Yuck’ face) from happy stimuli (i.e., ‘Smile’ face), an approach that could be leveraged for studying valence in addition to emotion‐specific responses.…”
Section: Discussionmentioning
confidence: 99%